The Relationship Between Pregnant Women's Obsession with Healthy Eating and Perceived Stress: Exploring the Impact of Healthy Eating Obsession on Stress in Pregnant Women - ADA, Güleser; CANİŞ, Cennet (Genius Journal, 2024)
Introduction: Pregnancy brings physical, psychological, and social changes, emphasizing health and nutrition. While healthy eating is vital, excessive concern can lead to unhealthy obsessions. Elevated stress during pregnancy may influence eating behaviors, making it crucial to explore their relationship. Objective: This study aimed to investigate the relationship between obsession with healthy eating and perceived stress in pregnant women. Methods: A cross-sectional study was conducted with 325 pregnant women attending Bartın Maternity and Children's Hospital between September 2023 and February 2024. Data were collected using the Pregnant Descriptive Information Form, Obsessions with Healthy Eating Scale (ORTO-11), and Perceived Stress Scale (PSS). Statistical analyses included descriptive statistics, the Mann-Whitney U test, and Spearman correlation tests. Results: The participants' mean age was 27.40±4.46 years, with a mean gestational age of 23.70±6.22 weeks and an average weight gain of 6.55±2.60 kg. Of the participants, 60.6% had a BMI of 25 and above. The mean ORTO-11 score was 24.69±2.58, and the mean PSS score was 34.08±3.05. There was no significant correlation between ORTO-11 and PSS scores. However, significant differences in perceived stress and ORTO-11 scores were observed concerning night eating, continuous diet programs, and eating habits outside the home. Conclusion: This study did not find a statistically significant relationship between pregnant women's obsession with healthy eating and their perceived stress levels. However, the findings suggest that maternal eating behaviors and stress may be influenced by factors such as social support and individual coping mechanisms.